ELEVEN LEVEL INVERTER DESIGN WITH DVR FOR DISTRIBUTION ENERGY SYSTEM - GN, SACHINAMREISS.; S, DINESHKUMAR. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
In this paper with ﬂexible AC transmission system capability is implemented. The proposed inverter is placed between the wind turbine and the grid, same as a regular WEI, and is able to regulate active and reactive power transferred to the grid. This inverter is equipped with dynamic voltage restorer option in order to control the power factor of the local feeder lines. The goal of this project is to introduce new ways to increase the penetration of renewable energy systems into the distribution systems. This will encourage the utilities and customers to act not only as a consumer, but also as a supplier of energy.